Pharmacokinetics of New Synthetic Heparin Mimetics - Hérault, J. P.; Bernat, A.; Roye, F.; Michaux, C.; Schaeffer, P.; Bono, F.; Petitou, M.; Herbert, J. M. (Thrombosis and Haemostasis, 2002)
Pharmacokinetics of oligosaccharides displaying various affinities for antithrombin (AT) allowed us to show that there was a close relationship between the plasma half-life of these antithrombotic oligosaccharides and their affinity for AT. Recently, we have described new heparin mimetics comprising an AT binding domain and a thrombin binding domain separated by a neutral methylated saccharide sequence. These compounds displayed strong anti-Xa and anti-IIA activities and, in contrast to heparin, escaped neutralisation by platelet factor 4. The aim of this work was to compare the pharmacokinetics of several of these heparin mimetics in rats. These compounds differed by their length, charge and affinity for AT (AT-binding domain). The results obtained indicate that the prolongation of the AT binding domain did not modify significantly their affinities for AT. However, an increase in the number of charges leads to a decrease in the half-life. When a methylated spacer was added in order to minimise the non-specific interactions to other proteins, half-lives of the heparin mimetic were in the same range than that of the pentasaccharide used as an AT binding domain.In conclusion, this study shows the influence of the charge of the oligosaccharides on their pharmacokinetics and underlines the importance of minimising their non-specific binding to plasma proteins in order to obtain compounds with predictive pharmacokinetics.
Keywords: Antithrombin; heparin; pentasaccharide